PERUBAHAN MODEL KOMUNIKASI DAN PERGESERAN PARADIGMA PEMBANGUNAN DALAM PERSPEKTIF SEJARAH (Paramita: Historical Studies Journal, 2014)
Communication has been stepped over a long development history. During its developing process, a communication is used as a strategy and a tool for supporting a successful development.  First, this paper describes a development of communication. Secondly, it will describe the conceptual-izetion of communication model and the third one is the application of communication model for each development paradigm model. Based on literary review, there are six stages in the history of communication development and three conceptual-izetion of communication models from hundreds model assumed by the experts.   The paradigm reshuffle is in line with the change of the application of communication model. Keywords: the history of communication, communication model, paradigm development Komunikasi telah melalui sejarah perkembangan yang panjang. Dalam proses perkembangannya, komunikasi dimanfaatkan sebagai strategi dan alat untuk mendukung keberhasilan pembangunan. Tulisan ini mendeskripsikan pertama, sejarah perkembangan komunikasi. Kedua, konseptualisasi model komunikasi dan ketiga penerapan model komunikasi dalam setiap model paradigma pembangunan. Berdasarkan tinjauan literatur terdapat enam tahapan dalam sejarah perkembangan komunikasi dan tiga konseptualisasi model komunikasi dari ratusan model yang dikemukakan oleh para ahli. Pergeseran paradigma pembangunan sejalan dengan perubahan penerapan model komunikasi. Kata kunci: sejarah komunikasi, model komunikasi, paradigma pembangunan